Clinical Features and Molecular Markers on Diffuse Midline Gliomas With H3K27M Mutations: A 43 Cases Retrospective Cohort Study - Wang, Yuan; Feng, Lan-lan; Ji, Pei-gang; Liu, Jing-hui; Guo, Shao-chun; Zhai, Yu-long; Sankey, Eric W.; Wang, Yue; Xue, Yan-rong; Wang, Na; Lou, Miao; Xu, Meng; et al. (Frontiers in Oncology, 2021)
Purpose Diffuse midline gliomas (DMG) with H3K27M mutations have been identified as a rare distinctive entity with unique genetic features, varied molecular alterations, and poor prognosis. The current study aimed to evaluate the clinical characteristics and profile of molecular markers on patients with a DMG harboring H3K27M mutations, and explore the impact of this genetic makeup on overall survival. Methods We retrospectively analyzed 43 consecutive patients diagnosed with a DMG harboring H3K27M mutations (age range 3 to 75 years) and treated in a tertiary institution within China between January 2017 to December 2019. Various clinical and molecular factors were evaluated to assess their prognostic value in this unique patient cohort. Results The median overall survival (OS) was 12.83 months. Preoperative Karnofsky Performance Score (KPS) and adjuvant radiotherapy were found to be independent clinical parameters influencing the OS by multivariate analysis (p = 0.027 and p < 0.001 respectively). Whereas extent of tumor resection failed to demonstrate statistical significance. For molecular markers, P53 overexpression was identified as a negative prognostic factor for overall survival by multivariate analysis (p = 0.030). Conclusion Low preoperative KPS, absence of radiotherapy and P53 overexpression were identified as predictors of a dismal overall survival in patients with DMG and H3K27M mutations.